2014
DOI: 10.1155/2014/701329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sufentanil Administration on Remifentanil-Based Anaesthesia during Laparoscopic Gynaecological Surgery: A Double-Blind Randomized Controlled Trial

Abstract: This study assessed the effect of sufentanil administered before conclusion of remifentanil-based anaesthesia on postoperative hyperalgesia and haemodynamic stability in patients undergoing laparoscopic gynaecological surgery. The patients were randomly allocated to a sufentanil administration group (S group) or a normal saline administration group (C group). Anaesthesia was induced and maintained with controlled administration of remifentanil at 10 ng·mL−1 and propofol under bispectral index guidance. Once th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Effective analgesia can reduce stress responses postsurgery, which in turn can facilitate better wound healing outcomes. 18,19 However, it is essential to consider the potential side effects associated with these opioids. As mentioned, the combination of ropivacaine with sufentanil has been associated with a higher incidence of pruritus and numbness, 1,20 which could impact patient comfort and overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective analgesia can reduce stress responses postsurgery, which in turn can facilitate better wound healing outcomes. 18,19 However, it is essential to consider the potential side effects associated with these opioids. As mentioned, the combination of ropivacaine with sufentanil has been associated with a higher incidence of pruritus and numbness, 1,20 which could impact patient comfort and overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous research that has emphasized the importance of optimal pain management in promoting wound healing. Effective analgesia can reduce stress responses postsurgery, which in turn can facilitate better wound healing outcomes 18,19 . However, it is essential to consider the potential side effects associated with these opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Son et al [26] reported that in patients undergoing GLS, sufentanil administered before the conclusion of remifentanil anaesthesia reduced postoperative hyperalgesia and achieved haemodynamic stability during extubation without delaying recovery or worsening PONV. Sufentanil administration during remifentanil-based complete intravenous anaesthetic induction is linked to lower early postoperative opioid use [27].…”
Section: Discussionmentioning
confidence: 99%
“…The standard visual analogue scale (VAS), ranging from 0 to 10 cm (0 means no pain;10 cm describes the worst pain imaginable), 22 was explained to the patients during the preoperative visit and the patients should slide the ruler every time the pain is assessed. A statistician who was unaware of the design of the study randomly and equally divided patients into two groups by using a computer-generated random number table: Test group (group T), 0.2μg/kg sufentanil (prepared by a independent anesthesiologist and diluted into 10mL) was given 1h before the end of the surgery; and Control group (group C), an equivalent volume of normal saline (prepared by the independent anesthesiologist and diluted into 10mL).…”
Section: Methodsmentioning
confidence: 99%